Impulsive Buying Among Tiktok Users: (Study on Gen Z) - Imam Gozali; Hidayah Sri Pamungkas (Digital Innovation : International Journal of Management, 2025)
This study aims to determine how much influence digital marketing strategies (content marketing, affiliate marketing and flash sales) have in encouraging impulsive purchasing behavior in Gen Z. The population of this study consists of all Generation Z TikTok users in Indonesia, with an unknown total number. The research method employed is a quantitative approach using a survey of 100 respondents selected through convenience sampling. The data were analyzed using multiple linear regression with inferential analysis or classical assumption testing. The results show that, partially, all three independent variables have a positive and significant effect on impulsive buying. Flash Sales have the greatest effectiveness influence, with a multiple regression coefficient value of 0.275. Although Flash Sales are statistically the most effective, descriptive analysis results indicate that affiliate marketing has the highest level of effectiveness based on the respondents’ average score of 21.69. Therefore, an optimal digital marketing strategy can leverage all three methods to enhance impulsive buying behavior.